Evaluation of climatic conditions from 1978 to 2020 of Oued Souf valley (Southern East of Algeria) - Barkat, Ayoub; Bouaicha, Foued; Rahal, Zakaria; Mester, Tamás; Szabó, György (Acta Geographica Debrecina Landscape & Environment series, 2023)
In this research, a climatic synthesis was built to assess the climatic parameters of the Oued Souf Valley through the meteorological data obtained from Guemar station (airport). It was revealed that the hydrological year of Oued Souf Valley is branded by the presence of a dry period and the total absence of a wet period over the year, even during January, when it was observed to have the lowest temperature and highest precipitation, which classified it as a Saharan climate (Hyper arid). The irregularity and the scarcity of precipitation, high temperatures and extremely high evapotranspiration had significant repercussions on surface runoff and infiltration which implies a high pressure on the water resources of Oued Souf valley and may disrupt the future socioeconomic project and increase the damage of natural drought and desertification.